From Normalisation to Partial Normalisation: Evaluating the Effectiveness of Antiretroviral Treatment in the Current Regime of Undetectable Equals Untransmittable - Ogunrotifa, Ayodeji Bayo (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
In the current global discourse on HIV, antiretroviral therapy has been effective in suppressing viral load to an undetectable level and rendering HIV non-infectious. Central to this discourse is the sociological idea that effective antiretroviral treatment has fostered normalisation of HIV in everyday life. This article explores the question of how people living with HIV in Nigeria evaluate the effectiveness of antiretroviral treatment in achieving normalization. Drawing on insights from the sociology of evaluation, it was found that patient’s evaluations of antiretroviral drugs differ from those of medical professionals and HIV experts. While HIV experts limit their definition of normalization to (a) being able to have unprotected sex and (b) being able to have HIV-negative children, HIV patients take other factors into account, such as the ability to breastfeed or to donate blood and organs. The findings revealed that promissory notes of effective antiretroviral treatment cannot foster complete normalisation in patients’ evaluations, but offer partial normalisation of HIV in everyday life, as biomedical intervention cannot nullify these risks and achieve HIV non-infectiousness completely. This finding has not only highlighted the gulf between lay and expert understanding of normalisation, but also uncovers the limit of the Swiss Consensus Statement and the shortcomings associated with the current global campaign and discourse that has prioritised undetectability equals untransmittability (#U=U).